Teacher’s Influence on Bullying Prevention in RA Al‑Muslimun: Practices and Outcomes in Bandung’s Early Childhood Education - Sopiyah, Sopiyah (Journal of Islamic Early Childhood Education (JOIECE): PIAUD-Ku, 2025)
This study examines the role of teachers in preventing bullying at RA Al-Muslimun, Bandung, focusing on strategies, challenges, and supporting factors in early childhood education. Bullying, often addressed seriously in higher educational levels, is still perceived as normal behavior in kindergartens. Using a qualitative approach, data were collected through observation, interviews, and documentation involving the principal and four teachers. Findings reveal that teachers act as role models, teaching good morals daily through structured activities such as moral recitations, storytelling, and songs highlighting exemplary behaviors. The forms of bullying identified include physical (hitting, kicking) and verbal (insults, ridicule). Challenges include inconsistent parenting styles, environmental influences, peer interactions, and the impact of social media. Supporting factors involve teacher competence, principal support, and collaborative teamwork among educators. The study concludes that effective bullying prevention in early childhood requires strong cooperation between teachers, parents, and schools, coupled with ongoing teacher training to enhance awareness and intervention skills.